Impact of urban agriculture on malaria vectors in Accra, Ghana - Klinkenberg, E.; McCall, P.; Wilson, M.D.; Amerasinghe, F.P.; Donnelly, M.J. (Malaria Journal (7): 151, 2008)
To investigate the impact of urban agriculture on malaria transmission risk in urban Accra larval and adult stage mosquito surveys, were performed. Local transmission was implicated as Anopheles spp. were found breeding and infected Anopheles mosquitoes were found resting in houses in the study sites. The predominant Anopheles species was Anopheles gambiae s.s.. The relative proportion of molecular forms within a subset of specimens was 86% S-form and 14% M-form. Anopheles spp. and Culex quinquefasciatus outdoor biting rates were respectively three and four times higher in areas around agricultural sites (UA) than in areas far from agriculture (U). The annual Entomological Inoculation Rate (EIR), the number of infectious bites received per individual per year, was 19.2 and 6.6 in UA and U sites, respectively. Breeding sites were highly transitory in nature, which poses a challenge for larval control in this setting. The data also suggest that the epidemiological importance of urban agricultural areas may be the provision of resting sites for adults rather than an increased number of larval habitats. Host-seeking activity peaked between 2-3 am, indicating that insecticide-treated bednets should be an effective control method.